1998
DOI: 10.1038/sj.onc.1201949
|View full text |Cite
|
Sign up to set email alerts
|

Distinct regions of allelic imbalance on chromosome 10q22-q26 in squamous cell carcinomas of the lung

Abstract: The genetic mechanisms underlying the progression to the metastatic phenotype of lung cancer are poorly understood. We recently showed that small cell lung cancer (SCLC) and metastasizing squamous cell carcinomas are characterized by an increased incidence of allelic loss on chromosome 10q. In the present study we performed a deletion mapping using 24 polymorphic markers on chromosome 10q22-q26 in 39 squamous cell carcinomas (SCC) of the lung identifying 14 metastatic carcinomas (74%) and three non-metastatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
2
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 24 publications
3
32
2
3
Order By: Relevance
“…It has been reported that alterations in more than one gene within the 10q22-10q26 region may be involved in human cancer development (1). In the present study, mutations in exon 15 of Ikk␣ were detected in human SCCs.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…It has been reported that alterations in more than one gene within the 10q22-10q26 region may be involved in human cancer development (1). In the present study, mutations in exon 15 of Ikk␣ were detected in human SCCs.…”
Section: Discussionsupporting
confidence: 49%
“…Previous studies have shown that Pten mutations are found frequently in human SCCs; however, these Pten mutations are not detected in all cases (1,2). p53 mutations have also been identified in a large proportion of human SCCs (3); however, these p53 mutations can be latent in skin cells for years before the onset of this disease.…”
Section: Ikk (I B Kinase)mentioning
confidence: 98%
“…Rashmi et al 33 found results with activating PIK3CA (E545K, E542K) and inactivating PTEN (R233) mutations were identified in human cervical cancer. An analysis of PTEN gene in squamous cell carcinomas from other sites also found that PTEN is not frequently mutated in the lung 34 , cervix 14 , skin 35 , head and neck 36 or esophagus 37 . Although numerous somatic mutations have been localized in the PTEN gene, these only occur in a minority of tumors, which indicates that alternative mechanisms of PTEN inactivation, both genetic and non-genetic, must exist.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple screening studies for genetic alterations in chromosome 10q in various cancers have frequently revealed two common minimally deleted regions in prostate tumors and other cancers (Cairns et al, 1997;Carter et al, 1990;Gray et al, 1995;Ittmann, 1996;Kim et al, 1998;Petersen et al, 1998). Table 1 summarizes the rates of LOH that have been detected with microsatellite markers within this region.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of heterozygosity (LOH) and homozygous deletions at human chromosomal regions 8p21 ± 22 and 10q23 ± 24 are frequently found in prostate adenocarcinomas, as well as other cancer tumors, and suggest that multiple TSGs are present in each of these locations Cairns et al, 1997;Carter et al, 1990;Gray et al, 1995;Ishii et al, 1999;Ittmann, 1996;Kagan et al, 1995;Kim et al, 1998;Li et al, 1997;Petersen et al, 1998;Whang et al, 1998).…”
Section: Introductionmentioning
confidence: 99%